Religiusitas Masyarakat Di Desa Bonto Mate’ne Pada Bulan Muharram - Asmira Dewi; Darman Manda (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
This research aims to find out and understand the meaning of the people in Bonto Mate'ne Village regarding the month of Muharram, to know and understand the process of welcoming the month of Muharram in Bonto Mate'ne Village and to know and understand the function and value of the month of Muharram in Bonto Mate'ne Village on people's religiosity. To achieve this goal, qualitative research methods were used by means of observation, interviews and documentation. The data that has been obtained is then analyzed and interpreted based on theory and relevant research results. The research results show that the month of Muharram is the beginning of the Islamic new year, the month of Muharram is highly revered and glorified among Muslims. The meaning of the people in Bonto Matene village in the month of Muharram as a month where they are not allowed to celebrate because it is based on the name of the month of Muharram in the Makassar language is called ma'rang which means crying hot sauce which is a bad analogy. In welcoming the month of Muharram, the people in Bonto Matene village perform the songkobala ritual and buy household tools such as brooms, ladles, basins, nyiru and pans. The function and value of the month of Muharram for the people of Bonto Matene village is that in the month of Muharram Muslims are prohibited from fighting and in the month of Muharram the reward or good deeds will be multiplied.